2020
DOI: 10.1002/acp.3719
|View full text |Cite
|
Sign up to set email alerts
|

Refining the blank line‐up procedure: How should we instruct eyewitnesses?

Abstract: Presenting a blank lineup-containing only fillers-to witnesses prior to showing a real lineup might be useful for screening out those who pick from the blank lineup as unreliable witnesses. We show that the effectiveness of this procedure varies depending on instructions given to witnesses. Participants (N = 462) viewed a simulated crime and attempted to identify the perpetrator from a lineup approximately one week later. Rejecting a blank lineup was associated with greater identification accuracy and greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Logically, if a witness chooses someone from the first lineup, they should be more likely to reject the second lineup based on commitment effects (e.g., Gorenstein & Ellsworth, 1980; Palmer et al, 2012). However, a recent study found minimal evidence of such logical shifts in decision criterion (Kucina et al, 2020). Such results—along with the present results and those of Palmer et al (2010)—suggest that more research is required to understand the factors that shape criterion setting in multiple lineup scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Logically, if a witness chooses someone from the first lineup, they should be more likely to reject the second lineup based on commitment effects (e.g., Gorenstein & Ellsworth, 1980; Palmer et al, 2012). However, a recent study found minimal evidence of such logical shifts in decision criterion (Kucina et al, 2020). Such results—along with the present results and those of Palmer et al (2010)—suggest that more research is required to understand the factors that shape criterion setting in multiple lineup scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Our research demonstrates the need to update current recommendations so that postidentification feedback is withheld not only until confidence has been recorded but also until there is no longer a possibility that the witness may be asked to view another lineup. This adjustment is especially important because, for various reasons, witnesses often view multiple lineups during police investigations (Horry et al, 2015; Kucina et al, 2020; Palmer et al, 2012; Smalarz et al, 2019; Steblay et al, 2013; Wells, 1984), and many of these cases involve multiple culprits (Hobson & Wilcock, 2011; Horry et al, 2014). Thus, there is considerable scope for feedback to increase the incidence of eyewitness misidentification in cases involving multiple culprits.…”
Section: Discussionmentioning
confidence: 99%